2017
DOI: 10.18666/jpra-2017-v35-i2-7363
|View full text |Cite
|
Sign up to set email alerts
|

Dreaming About Access: The Experiences of Transgender Individuals in Public Recreation

Abstract: There has been little research about transgender individuals and their needs, especially within leisure settings (Grossman, O 'Connell, & D'Augelli, 2005;Lewis & Johnson, 2011). Nevertheless, public recreation agencies are responsible for ensuring that all of the citizens they serve have equitable access to leisure facilities and programming. Additional research is needed to understand the barriers, needs, and wants of the transgender community. The purpose of this study was to explore the experience of transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…While having these physical spaces in campus recreation facilities is important, the ability for managers to utilize these spaces effectively is also imperative. The presence of gender-inclusive spaces should be clearly communicated to participants and staff, and the regulations regarding their use should be well understood as these spaces do not solely benefit LGBTQ participants (Oakleaf & Richmond, 2017). The presence of gender-inclusive spaces should not inhibit the integration of LGBTQ participants into other normative, gendered spaces.…”
Section: Discussionmentioning
confidence: 99%
“…While having these physical spaces in campus recreation facilities is important, the ability for managers to utilize these spaces effectively is also imperative. The presence of gender-inclusive spaces should be clearly communicated to participants and staff, and the regulations regarding their use should be well understood as these spaces do not solely benefit LGBTQ participants (Oakleaf & Richmond, 2017). The presence of gender-inclusive spaces should not inhibit the integration of LGBTQ participants into other normative, gendered spaces.…”
Section: Discussionmentioning
confidence: 99%
“…From our perspective, this ignores the impact exclusion from sports and recreation has on transgender people 68‐70 . The much larger “problem” of transgender individuals and sport is the exclusion of transgender people, whether explicitly through legislative bans or through discrimination, bias, and harassment directed toward transgender people.…”
Section: Role Of Pmandr In Lgbtqia+ Healthmentioning
confidence: 98%
“…From our perspective, this ignores the impact exclusion from sports and recreation has on transgender people. [68][69][70] The much larger "problem" of transgender individuals and sport is the exclusion of transgender people, whether explicitly through legislative bans or through discrimination, bias, and harassment directed toward transgender people. Further, much of the debate remains focused on transgender women participating in women's sports with a notable absence of discussion of transgender men in sports.…”
Section: Advocate For Transgender People In Sports and Recreationmentioning
confidence: 99%
“…For example, Jones et al ( 2017a ) found evidence of structural barriers to participation and a lack of inclusion through their critical scrutiny of sport policies ( n = 31), and their review of existing academic research findings ( n = 8). Pérez-Samaniego et al ( 2019 ) provide valuable focus on existing qualitative studies ( n = 12), highlighting shared findings of exclusionary processes such as abjection (Travers and Deri, 2011 ; Lucas-Carr and Krane, 2012 ), use of language (Semerjian and Cohen, 2006 ; Sykes, 2009 ), design of space and facilities (Lewis and Johnson, 2011 ; Van Ingen, 2011 ; Oakleaf and Richmond, 2017 ).…”
Section: Inequality: Conceptual Framingmentioning
confidence: 99%